Peran Semen Portland Tipe I dan Portland Komposit Atas Ketidaksesuaian Perkembangan Kuat Tekan Pada Beton Normal Terhadap PBI 1971 - Yonanda, Prima Sandy; DWSBU, Chatarina Niken; Noorhidana, Vera Agustriana (Universitas Lampung, 2020)
The code about concrete compressive strength progress is presented on Table 4.1 of PBI 1971. But the concrete compressive strength development in many current concrete construction projects often face one similar major problem which is the incompability between concrete compressive strength progress compared to PBI 1971. To identify that problem, this research was done by creating 160 cube concrete samples from OPC and 120 cube concrete samples from PCC by using 4 different PCC and OPC brands that consist of Dynamix, Baturaja, Tigaroda and Padang. Moreover, the samples are consists of 2 different targeted concrete compressive strength which are K250 and K400 and the samples were tested in the age of 7, 14, 21, 28 and 56 days. Aside of that, the chemical properties in each of used cements that consist of Tricalcium Silicate (C3S), Dicalcium Silicate (C2S), Tricalcium Aluminate (C3A) and Tetracalcium Aluminoferrit (C4AF) were also tested to identify the impact of chemical properties of cements to the compressing strength progress of all samples.Based on the research, it was identified that the chemical properties of cements that consist of C3S, C2S, C3A and C4AF were very influential in the process of compressive strength progress of all samples. In addition, the coeffiecients presented on SNI-15-2049-2015 Chapter 5 Table 5 used to calculate the percentage of C3S, C2S, C3A and C4AF need further reviews. Last, it was known that the compressing strength development of both OPC and PCC samples were not aligned to the PBI 1971 estimation. Besides, the procedure of all samples have followed the British Standard and ASTM regulation. In conclution, based on the research PBI 1971 was no longer relevant to be used as the reference for concrete compressing strength progress. Keywords: Concrete, compressive strength progress, cement chemical properties, incompability, tricalcium silicate, dicalcium silicate, tricalcium aluminate, tetracalcium aluminoferrite.